1989
DOI: 10.1085/jgp.94.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of contraction initiated by flash photolysis of caged adenosine triphosphate in tonic and phasic smooth muscles.

Abstract: Laser flash photolysis of caged adenosine triphosphate (ATP), in the presence of Ca ~+, was used to examine the time course of isometric force development from rigor states in glycerinated tonic (rabbit trachealis) and phasic (guineapig ileum and portal vein) smooth muscles. Photolytic liberation of ATP from caged ATP initiated force development, at 20~ with half-time (t1#2) of 5.4 s in trachealis and 1.2-2.2 s in the phasic muscles. Prior to photolysis, some muscles were phosphorylated with ATP plus okadalc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 26 publications
(34 reference statements)
2
51
0
Order By: Relevance
“…Briefly, 1 g of human bladder total RNA (BD Clontech), in a total reaction volume of 20 l, was reverse transcribed with oligo(dT) [12][13][14][15][16][17][18] primer, Superscript II, and RNAguard ribonuclease inhibitor (Amersham Pharmacia). Primers flanking the hypothetical region containing the code for the insert were designed from human (Ϫ)insert SMMHC (GenBank accession no.…”
Section: Sequencing Of Human Smmhc Insert Cdnamentioning
confidence: 99%
“…Briefly, 1 g of human bladder total RNA (BD Clontech), in a total reaction volume of 20 l, was reverse transcribed with oligo(dT) [12][13][14][15][16][17][18] primer, Superscript II, and RNAguard ribonuclease inhibitor (Amersham Pharmacia). Primers flanking the hypothetical region containing the code for the insert were designed from human (Ϫ)insert SMMHC (GenBank accession no.…”
Section: Sequencing Of Human Smmhc Insert Cdnamentioning
confidence: 99%
“…If the in situ temperature dependency of MLCK and MLCP were the same, one would predict that lowering temperature would not increase net MRLC phosphorylation in response to a specific stimulus-induced elevation in myoplasmic Ca 2+ . It has been reported that MLCK/MLCP activity ratio are higher in phasic smooth muscles than in tonic smooth muscles [17,22]. Blumenthal and Stull [23] reported that Q10 of MLCK equal to 2, whereas Q10 of myosin light chain phosphatase equal to 5.2 [13,24].…”
Section: Camentioning
confidence: 99%
“…The experimental apparatus and optimal conditions for 3 0 -deac-edaADP loading of smooth muscle bundles have been described in detail (Khromov et al 2004). Smooth muscle myosin A. V. Somlyo and others 1925 Different properties of phasic (fast) and tonic (slow) smooth muscles are inherent to their myosin isoforms (Horiuti et al 1989) and are apparent in the faster rate of force development in phasic than tonic muscles with thiophosphorylated RLCs. It was therefore of interest to compare ADP release rates of the two classes of smooth muscle.…”
Section: Adenosine Diphosphate Release and Its Modulation By Strain Amentioning
confidence: 99%
“…These properties are most prominent in tonic smooth muscles such as in blood vessels which maintain a high resting tone or maintain prolonged changes in blood flow. As noted above, distinct properties of tonic and phasic smooth muscle myosins relate to their myosin isoforms (Horiuti et al 1989). The major differences in nucleotide binding and release kinetics are thought to reflect the presence (in phasic) or absence (in tonic) smooth muscle myosin of a seven amino acid insert in the myosin heavy chain (Lauzon et al 1998).…”
Section: Physiological Relevance Of Adenosine Diphosphate Binding In mentioning
confidence: 99%